Hollow microcapsules by stitching together of graphene oxide nanosheets with a di-functional small molecule. (September 2016) - Luo, Qinmo; Wei, Peiran; Pentzer, Emily
Abstract: Micron-sized hollow capsules composed of graphene oxide and small molecule cross-linker are prepared and isolated. These capsules are thoroughly characterized using various spectroscopic and microscopic techniques. The cross-linked and non-cross-linked microcapsules show distinct release profiles from each other. Moreover, the microcapsules can be loaded with gold nanoparticles, suggesting these structures are useful in encapsulation technologies.